Bentuk Komunikasi Politik untuk Membangun Perilaku Politik Masyarakat Lokal Guna Menciptakan Pemilukada yang Aman - Setyarahajoe, Ratna (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2013)
The practice of election should be an important momentum for local people to directly elect the head of terrain. This election studies conducted by the National Law Reform Consortium concluded, that the celebration of democracy in 2010 "to lose their meaning, since the practice of money politics and the politicization of the bureaucracy that dominates the process of winning the election". With the scenario of fraud in the election, it can be a catalyst for conflict between supporters of candidates, which often leads to conflicts that are anarchists. For that we need a form of political communication that can shape political behavior so that local communities can safe and clean election.